A case of heart failure mimicking COVID-19 pneumonia: The role of clinical and chest computed tomography findings in the differential diagnosis - MUTLU, BÜLENT; ATAŞ, HALİL (AVES, 2020)
Acute heart failure (HF) is one of the most common cardiac emergencies. Pulmonary edema caused by HF may mimic an exudative disease on chest computed tomography scans. Coronavirus disease 2019 (COVID-19) emerged in China in December 2019 and quickly spread around the world. During this pandemic period, the need to exclude the possibility of COVID-19 pneumonia in patients with acute dyspnea may cause a delay in the diagnosis and treatment of patients with acutely decompensated HF who have similar symptoms. This case report describes a diabetic patient admitted with dyspnea one week after she suffered an acute myocardial infarction. The objective of this report is to draw attention to the differential diagnosis of HF and COVID-19 pneumonia.
Keywords: COVID-19; heart failure; pneumonia; CORONAVIRUS